2015
DOI: 10.1149/2.0121512jss
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ni-YSZ by Atomic Layer Deposition

Abstract: Nickel yttria-stabilized zirconia (Ni-YSZ) is used as anode material for solid oxide fuel cells (SOFCs). The electrochemical performance of Ni-YSZ anodes can be improved when the size of constituent particles of nickel is reduced. However, at SOFC high temperature operating environments, nano-sized Ni particles suffer from sintering. Nanoscale Ni-YSZ anodes can undergo severe structure changes. In this work, a unique approach of fabricating a nanostructured Ni-YSZ anode is demonstrated by combining atomic laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The study also suggested that the improvement is doable with other catalytic metals such as Ni, Cu, and Co. Meanwhile, ALD has been used with the glancing angle deposition (GLAD) technique to prevent the sintering of the Ni at high temperature 69 . ALD was used to deposit a nanoscale YSZ layer uniformly and to stabilize the Ni particles.…”
Section: Anode Fabrication Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study also suggested that the improvement is doable with other catalytic metals such as Ni, Cu, and Co. Meanwhile, ALD has been used with the glancing angle deposition (GLAD) technique to prevent the sintering of the Ni at high temperature 69 . ALD was used to deposit a nanoscale YSZ layer uniformly and to stabilize the Ni particles.…”
Section: Anode Fabrication Methodsmentioning
confidence: 99%
“…Meanwhile, ALD has been used with the glancing angle deposition (GLAD) technique to prevent the sintering of the Ni at high temperature. 69 ALD was used to deposit a nanoscale YSZ layer uniformly and to stabilize the Ni particles. Besides, it can provide an ionic conductive phase.…”
Section: Chemical Deposition Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…[ 215 ] However, the electrochemical performance cathode drops at low operating temperature due to poor oxygen reduction reaction (ORR). Surface modification of thermally stable metal oxides such as doped ZrO 2 , [ 216 ] CeO x , [ 217 ] Al 2 O 3 , [ 218 ] TiO x , [ 219 ] and SnO x , [ 220 ] perovskite‐based cathodes materials ((Mn 0.8 Co 0.2 ) 3 O 4 , [ 221 ] Pr 6 O 11 [ 222 ] ), and metals (pure and alloys) (Pt, [ 223 ] Ru, [ 224 ] Pd, [ 225 ] Ni, [ 226 ] Al, [ 227 ] PtRu, [ 228 ] NiPd, [ 225 ] NiRu [ 229 ] ) have been engineered via the ALD technique. These nanostructured coatings/electrode materials are proven to be effective in stabilizing the catalyst surface without sacrificing the surface activity.…”
Section: Ald In Fuel Cellsmentioning
confidence: 99%